Synthesis of green zinc‐oxide nanoparticles and its dose‐dependent beneficial effect on spermatozoa during preservation: sperm functional integrity, fertility and antimicrobial activity - Lyngdoh, Meiaishan Eliezer; Chettri, Jyoti; Kharchandy, Vivian F.; Sheel, Rishav; Choudhury, Arnab Roy; Sarkar, Biplab; Pattanayak, Arunava; Deori, Sourabh; Abedin, Sayed Nabil; Kadirvel, G. (Frontiers in Bioengineering and Biotechnology, 2024)
This study demonstrates the beneficial effect of zinc oxide nanoparticles (ZnO-NPs) as an additive to semen extender to improve semen quality, fertility and antibacterial activity during liquid preservation in a boar model.Initially to find out the safe concentration of ZnO-NPs in sperm cells, a wide range of ZnO-NPs concentrations (0, 5, 10, 50, 100, 500 and 1000 μM) was co-incubated with sperm at 37°C for cytotoxic study. These NP concentrations were compared to their salt control zinc acetate (ZA) at the same concentrations and to a control group. The effect of the different concentrations of ZnO-NPs on sperm motility, membrane integrity, mitochondrial membrane potential (MMP) and apoptosis was assessed. Accordingly, the non-toxic dose was selected and supplemented in MODENA extender to determine its beneficial effect on boar semen parameters mentioned and the lipid peroxidation (LPO) levels during liquid preservation at 16 °C for 6 days. Antibacterial study of ZnO-NPs and its salt control at doses of 10 μM and 50 μM was carried out by CFU method.The cytotoxic study revealed that 5, 10 and 50 μM of ZnO-NPs are safe. Consequently, semen preserved in the MODENA extender, incorporating the non-toxic dose, exhibited 10 and 50 μM ZnO-NP as the optimal concentrations for beneficial outcomes during liquid preservation at 16°C. 10 μM ZnO-NP resulted in a significantly (p<0.05) improved conception rate of 86.95 % compared to the control of 73.13 %. 10 and 50 μM ZnO-NPs exhibit potent antimicrobial action by reducing the number of colonies formed with days of preservation in comparison to the negative control. The investigation concluded that the incorporation of 10 μM ZnO-NPs led to enhancements in sperm motility, membrane integrity, and sperm mitochondrial membrane potential (MMP), attributed to a reduction in malondialdehyde (MDA) levels. This improvement was accompanied by a concurrent increase in fertility rates, including farrowing rate and litter size, during the liquid preservation process. Furthermore, ZnO-NPs exhibited an antimicrobial effect, resulting in decreased bacterial growth while preserving boar semen at 16°C for a duration of 6 days.These findings suggest that ZnO-NPs could serve as a viable alternative to antibiotics,